Two Pathways of Sphingolipid Biosynthesis Are Separated in the Yeast Pichia pastoris - Ternes, Philipp; Wobbe, Tobias; Schwarz, Marnie; Albrecht, Sandra; Feussner, Kirstin; Riezman, Isabelle; Cregg, James M.; Heinz, Ernst; Riezman, Howard; Feussner, Ivo; Warnecke, Dirk (The Journal of biological chemistry, 2011)
Although the yeast Saccharomyces cerevisiae has only one sphingolipid class with a head group based on phosphoinositol, the yeast Pichia pastoris as well as many other fungi have a second class, glucosylceramide, which has a glucose head group. These two sphingolipid classes are in addition distinguished by a characteristic structure of their ceramide backbones. Here, we investigate the mechanisms controlling substrate entry into the glucosylceramide branch of the pathway. By a combination of enzymatic in vitro studies and lipid analysis of genetically engineered yeast strains, we show that the ceramide synthase Bar1p occupies a key branching point in sphingolipid biosynthesis in P. pastoris. By preferring dihydroxy sphingoid bases and C16/C18 acyl-coenzyme A as substrates, Bar1p produces a structurally well defined group of ceramide species, which is the exclusive precursor for glucosylceramide biosynthesis. Correlating with the absence of glucosylceramide in this yeast, a gene encoding Bar1p is missing in S. cerevisiae. We could not successfully investigate the second ceramide synthase in P. pastoris that is orthologous to S. cerevisiae Lag1p/Lac1p. By analyzing the ceramide and glucosylceramide species in a collection of P. pastoris knock-out strains in which individual genes encoding enzymes involved in glucosylceramide biosynthesis were systematically deleted, we show that the ceramide species produced by Bar1p have to be modified by two additional enzymes, sphingolipid Δ4-desaturase and fatty acid α-hydroxylase, before the final addition of the glucose head group by the glucosylceramide synthase. Together, this set of four enzymes specifically defines the pathway leading to glucosylceramide biosynthesis.